Evaluation of Periapical Radiolucency and Periodontal Bone Loss of Endodontically Treated Teeth Before and After Orthodontic Treatment Using Cone Beam Computed Tomography - P. Narayana Prasad; Kanika Sharma; Hardeep Kaur; Mohd Amjad Tahseen; Somya Gupta; Shabina Shafi; Mrunal Meshram (Journal of Pharmacy and Bioallied Sciences)
Background: The impact of using orthodontic therapy on the periapical radiolucency (PR) and alveolar bone loss in teeth that have received endodontic treatment has not been examined in any prior research. Aim: This study used cone-beam computed tomography (CBCT) to assess alveolar bone loss and PR surrounding endodontic treated teeth (ETT) both before and after orthodontic therapy. Methods and Materials: This study was conducted involving 450 patients with ETT undergoing orthodontic treatment. The clinical and radiographic records of all patients included in this study were evaluated. Details regarding demographics, duration of orthodontic treatment, number of ETT, location of ETT, size of PR, alveolar bone dimension in ETT using CBCT. Results: It was observed that overall there was a decrease in the size of periapical lesion (PL) after orthodontic applaince (OA), however, the findings were not statistically significant. (P = 0.316). When there was the evaluation of alveolar bone loss, then it was observed that there was a decrease in the dimension of alveolar bone. Conclusion: There was a decrease in the size of the periapical lesion and dimensions of the alveolar bone around ETT after orthodontic treatment.